1997
DOI: 10.1590/s0037-86821997000300007
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação clínica do quinino para o tratamento de malária por Plasmodium falciparum

Abstract: O quinino foi o primeiro medicamento correntemente usado para tratar malária, tendo sido abandonado seu emprego principalmente após o início do emprego da cloroquina. A partir da década de 60 com o surgimento de resistência do P. falciparum à cloroquina voltou-se a utilizar o quinino isolado ou em associação para tratar tal infecção. Com o objetivo de avaliar clinicamente a resposta ao quinino de pacientes com malária por P. falciparum, analisamos os prontuários de 484 pacientes atendidos no Laboratório de Mal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
3

Year Published

1999
1999
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 2 publications
1
10
0
3
Order By: Relevance
“…However, its synthetic production by industrial means is both complex and costly. Quinine is still used today, and it is currently derived by extraction from the Cinchona spp., which grow wild in South America and are cultivated in Java (Boulos et al 1997).…”
Section: Plant-derived Antimalarial Agentsmentioning
confidence: 99%
“…However, its synthetic production by industrial means is both complex and costly. Quinine is still used today, and it is currently derived by extraction from the Cinchona spp., which grow wild in South America and are cultivated in Java (Boulos et al 1997).…”
Section: Plant-derived Antimalarial Agentsmentioning
confidence: 99%
“…For malaria, especially in the book by Pereira et al (2009), the statement was found that drugs containing quinine and derivatives can help prevent the disease, but Boulos et al (1997) warn of the toxic effects that quinine can cause in the organism and the low effect that it has if administered for fewer than 7 days. These facts are not detailed in the analyzed book.…”
Section: Discussionmentioning
confidence: 99%
“…Dentre eles, 13 (33%) investigaram algum tratamento previsto no protocolo oficial 16,17,18,19,20,21,22,23,24,25,26,27,28 . A Tabela 2 mostra que dos 2 fármacos isolados e das 5 associações medicamentosas recomendadas pelo protocolo oficial, apenas 4, entre ambas as categorias, foram avaliadas em estudos nacionais.…”
Section: Artigos Brasileiros Contemplando Fármacos E Associações Recounclassified
“…Seis, dentre os treze estudos identificados, foram publicados antes de 2001 16,20,23,24,25,27 , sendo, portanto, potenciais fontes de informação para a elaboração do Manual de Terapêutica da Malária. Cinco são trabalhos originais e um é revisão narrativa -não sistemática, e assim, não classificável (Tabela 1).…”
Section: Artigos Brasileiros Contemplando Fármacos E Associações Recounclassified